2003
DOI: 10.1097/00006199-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Parturient???s Positions and Perceptions of Labor Pain Intensity

Abstract: The sitting position offers an effective method to relieve lower back labor pain during cervical dilatation from 6 to 8 centimeters. Similar relief was experienced for women who reported pain only on contraction as well as those with continuous pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
4
18
1
2
Order By: Relevance
“…Those in the control arm did not receive similar interactions. Upright positions during labor have been associated with both shorter labors and also with increased capacity to cope with labor pain (Adachi, Shimada, & Usui, 2003; Lawrence, Lewis, Hofmeyr, Dowswell, & Styles, 2009). The higher average quantity of time upright during labor (181.3 minutes vs. 115.8 minutes, p =0.001) noted in those randomized to the experimental arm confounds interpretation of the birth ball exercise program on childbirth self-efficacy and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Those in the control arm did not receive similar interactions. Upright positions during labor have been associated with both shorter labors and also with increased capacity to cope with labor pain (Adachi, Shimada, & Usui, 2003; Lawrence, Lewis, Hofmeyr, Dowswell, & Styles, 2009). The higher average quantity of time upright during labor (181.3 minutes vs. 115.8 minutes, p =0.001) noted in those randomized to the experimental arm confounds interpretation of the birth ball exercise program on childbirth self-efficacy and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Randomized studies that evaluated the change in position reported a reduction in pain scores and an increase in comfort and satisfaction of mothers who have adopted the upright position (Adachi, Shimada, & Usui, 2003;Miquelutti, Cecatti, Morais, & Makuch, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 9 randomized controlled trials were included in the systematic review, with a total of 2,220 women [2,8-15] (Figure 1). None of the studies excluded from the review were randomized controlled trials [1,16-22] and one referred only to the second stage of labor [23]. Main characteristics of studies included in the review are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%